Mental Health First dalam Kepemimpinan Generasi Z: Studi Kasus pada Waroeng Searah di Tanjungpinang - Nabilla Firda Ramadhani; Syafika Dwi Syahwitri; Masiani Hia; Adinda Monica Prachelya; Satriadi Satriadi (Journal of Economics and Management Scienties, 2026)
Mental health in the workplace has become an increasingly important issue due to rising work pressures and the growing dominance of Generation Z in the workforce. This study aims to analyze the leadership style of the owner of Waroeng Searah from a Generation Z perspective by integrating the concept of mental health first. The study employed a descriptive qualitative approach using a case study method. Data were collected through observations and interviews with the owner of Waroeng Searah and a senior employee. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the owner applies a transformational leadership style characterized by open communication, non-hierarchical relationships, employee involvement in decision-making, and the creation of a supportive and comfortable work environment. Furthermore, excessive work pressure was not identified, while employee turnover was primarily influenced by external factors. However, the implementation of mental health first has not yet been carried out systematically and proactively. These findings highlight the importance of integrating mental health first principles into leadership practices and human resource management, particularly within Micro, Small, and Medium Enterprises (MSMEs).